Tiyo Soga: Violence, disruption and dislocation in the white polis - Vellem, Vuyani S. (HTS teologiese studies, 2016)
Tiyo Soga must be celebrated as he is the personification of a body of knowledge pertinent to the development of foundational knowledge in examining the violence, disruptions and dislocations of the bodies, knowledge and spirit in modernity. The question of skill and memory cannot be dichotomised in epistemologies of justice—the naming of black as pagan, kaffir, native, bantu, etcetra, in the history of oppression. Spatial justice, the article argues, is not just about physical space; it is about spiritual and temporal spaces as well. The linearity of time cannot do justice for the memory of the conquered. Land, the article argues, by inserting the memory of Tiyo Soga, is central to spatial justice as long as the ‘wedding’ between the troublesome Bible and the genocidal, epistemicidal and spirtualicidal forms of knowledge is debunked.